Antifungal and antimycotoxigenic activity of hydrolyzed goat whey on Penicillium spp: An application as biopreservation agent in pita bread. (January 2020) - Luz, Carlos; Izzo, Luana; Ritieni, Alberto; Mañes, Jordi; Meca, Giuseppe
Abstract: Whey is a by-product of the cheese industry, yet it contains proteins that have a high nutritional value and are an important source of antifungal peptides. Food deterioration caused by toxigenic fungi is one of the challenges of food safety. In this context, trypsin was used to hydrolyse goat milk whey at 37. The resultant peptides were characterised by LC–ESI–TOF-MS. Antifungal activity of the goat milk whey hydrolysate (HGW) was determined against 10 toxigenic fungi from the genus Penicillium, in solid and liquid media. Furthermore, HGW was used as an ingredient for bread elaboration. Bread elaborated with HGW and inoculated with toxigenic fungi was included in a shelf-life study of the reduction of fungal growth, mycotoxin production and the use of the additive calcium propionate in bread. A total of 27 peptides from α-lactalbumin, β-lactoglobulin, κ-casein and lactoferrin were identified. HGW evidenced fungal growth inhibition and presented minimum inhibitory concentration and minimum fungicidal concentration ranges of 3.9–62.5 and 15.8–250 g HGW/L, respectively. Bread with HGW displayed a 1-log reduction of fungal growth, 85–100% mycotoxin production, and extended the shelf-life by 2 days. Highlights: Antifungal activity of hydrolyzed cow whey against Penicillium spp. Identification of antifungal peptides through LC-ESI-MS-TOF. Improve shelf life of pita bread using hydrolyzed whey as a formulation ingredient.